Chromium speciation in foodstuffs: a review - Hamilton, Elliott M.; Young, Scott D.; Bailey, Elizabeth H.; Watts, Michael J. (Elsevier, 2018)
Numerous critical reviews have evaluated exposure to toxic and carcinogenic hexavalent chromium (Cr(VI)) from a number of pathways; including workplace air, cement and packaging materials. The contribution of foodstuffs to dietary Cr(VI) has been increasingly under investigation, however no summary of this work has been carried out. The objective of this article is to review the last twenty years of chromium speciation research in foodstuffs. Alkaline extraction, used for chromium speciation in other solids, is the most widely-reported procedure. Previous measurement of Cr(VI) in foodstuffs is questionable due to the reducing power of organic matter and antioxidants, leading to the development of speciated isotope dilution mass spectrometry (SIDMS) techniques to monitor interconversions. Evaluation of the genotoxicity of trivalent chromium (Cr(III)), which acts through a different pathway to that of Cr(VI), requires reconsideration towards measurement of Cr(III), which is present at higher concentrations in foodstuffs following reduction of the more-bioavailable Cr(VI).